How users matter : the co-construction of users and technologies - Oudshoorn, Nelly, 1950-; Pinch, T. J. (Trevor J.), 1952-2021 (Cambridge : MIT, 2003)
Users have become an integral part of technology studies. The essays in this volume look at the creative capacity of users to shape technology in all phases, from design to implementation. Using a variety of theoretical approaches, including a feminist focus on users and use (in place of the traditional emphasis on men and machines), concepts from semiotics, and the cultural studies view of consumption as a cultural activity, these essays examine what users do with technology and, in turn, what technology does to users. The contributors consider how users consume, modify, domesticate, design, reconfigure, and resist technological development--and how users are defined and transformed by technology. The book first shows how resistance to and non-use of a technology can be a crucial factor in the eventual modification and improvement of that technology, then looks at advocacy groups and the many kinds of users they represent, particularly in the context of health care and clinical testing. Finally, it examines the role of users in different phases of the design, testing, and selling of technology. Included here is an enlightening account of one company's design process for men's and women's shavers, which resulted in a "Ladyshave" for users assumed to be technophobes.
Keywords: Innovatie